Improvement in cardio-metabolic health and immune signatures in old individuals using daily chores (Salat) as an intervention: A randomized crossover study in a little-studied population - Alam, Iftikhar; Ullah, Riaz; Jan, Attaullah; Sehar, Bismillah; Khalil, Atif Ali Khan; Naqeeb, Huma; Ali, Essam A.; Wahab, Qazi Muhammad Farooq; Safdar, Mahpara; Ali, Abid; Zaman, Muhammad Haidar; Zeb, Falak (Frontiers in Public Health, 2022)
Background: Decline in cardio-metabolic health, immunity and physical activity are associated with old age. Old people also find it difficult to engage in structured exercise. Therefore, there is a need to investigate common daily chores as an alternative for exercise that also may help in maintaining cardio-metabolic and immune health. Objective: We aimed to investigate whether Salat, an obligatory Islamic prayer involving various physical movements and closely resembling yoga, enhance the benefits conferred by current guidelines for physical activity. Methods: A total of 30 overweight adults (mean (SD) age 53.5 (8.7) years) participated in this study. For 4-week duration, we compared effects of Salat before/after meals (Pre-MS/Post-MS) on selected immunological and metabolic parameters in serum samples. We also compared effects of both Pre-MS/Post-MS regimens in young and old subjects to see any age-related effects. Results: Most of baseline metabolic parameters and count of immune cells were normal. Post-MS resulted in significant reduction in body weight and percent body fat (%BF). Overall, Post-MS resulted in a clear leukocytosis with numerical increases of granulocytes, monocytes and lymphocytes. When analyzing lymphocyte compartment, clear numerical increases were noted for T, B and NK cells. The CD8+ T cell numbers showed statistical significant increase after exercise. Similarly, a Post-MS induced leukocytosis in both young and old individuals, while increases in granulocytes, monocytes and lymphocytes were statistically significant in old subjects only. Conclusions: This study demonstrated that the Islamic obligatory and congressional Salat practice is capable of mimicking desirable pro-immune and pro-metabolic health effects.